The Mechanism of Rac1 in Regulating HCC Cell Glycolysis Which Provides Underlying Therapeutic Target for HCC Therapy - Ren, Yin-Xiang; Li, Xiao-Bin; Liu, Wei; Yang, Xu-Guang; Liu, Xin; Luo, Yu (Journal of oncology, 2022)
Aim. To explore the role of Rac1 on sorafenib resistance in hepatocellular carcinoma. Methods. CCK-8, wound healing assay, Transwell, and cell cycle assay were used to detect the tumor cells development. Cell viability was assessed by MTT. The glycolytic pathway was revealed by cellular metabolism assays. Result. We recovered that Rac1 upregulation was related to HCC patients’ poorer prognosis. Forced expression of Rac1 promoted cell development and sorafenib chemoresistance in HCC cells. Rac1 inhibitor EHop-016 and sorafenib combination markedly prevented cell viability, G2/M phase cycle arrest, and apoptosis than single therapy. Furthermore, combination therapy decreased glycolysis in HCC cells. In vivo, the tumor growth was significantly prevented by combination therapy single therapy. Conclusion. Our research declares that Rac1 inhibition could block sorafenib resistance in HCC by decreasing glycolysis, which would provide an underlying target for HCC therapy.